2009
DOI: 10.1007/s11145-009-9173-y
|View full text |Cite
|
Sign up to set email alerts
|

Component processes of early reading, spelling, and narrative writing skills in Turkish: a longitudinal study

Abstract: The study examined: (a) the role of phonological, grammatical, and rapid automatized naming (RAN) skills in reading and spelling development; and (b) the component processes of early narrative writing skills. Fifty-seven Turkish-speaking children were followed from Grade 1 to Grade 2. RAN was the most powerful longitudinal predictor of reading speed and its effect was evident even when previous reading skills were taken into account. Broadly, the phonological and grammatical skills made reliable contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
88
4
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 63 publications
(87 reference statements)
14
88
4
14
Order By: Relevance
“…These findings are in line with those of previous studies (e.g., Furnes & Samuelsson, 2011;Moll et al, 2014;Wimmer & Mayringer, 2002). Despite the shortlived importance of phonological awareness as a predictor of reading in Finnish (e.g., Silvén, Poskiparta, Niemi, & Voeten, 2007;Torppa et al, 2015) and in other transparent orthographies (e.g., Georgiou, Parrila, & Papadopoulos, 2008;Mann & Wimmer, 2002), it has been shown to be an important predictor of spelling (e.g., Babayiğit & Stainthorp, 2010;Caravolas et al, 2012;Furnes & Samuelsson, 2011). The importance of phonological awareness in general and phoneme identification in particular is easy to understand in the case on Finnish.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with those of previous studies (e.g., Furnes & Samuelsson, 2011;Moll et al, 2014;Wimmer & Mayringer, 2002). Despite the shortlived importance of phonological awareness as a predictor of reading in Finnish (e.g., Silvén, Poskiparta, Niemi, & Voeten, 2007;Torppa et al, 2015) and in other transparent orthographies (e.g., Georgiou, Parrila, & Papadopoulos, 2008;Mann & Wimmer, 2002), it has been shown to be an important predictor of spelling (e.g., Babayiğit & Stainthorp, 2010;Caravolas et al, 2012;Furnes & Samuelsson, 2011). The importance of phonological awareness in general and phoneme identification in particular is easy to understand in the case on Finnish.…”
Section: Discussionsupporting
confidence: 91%
“…doi:10.1007/s11881-016-0131-5 2017 Final Draft in a Highly Consistent Orthography Good readers tend to be good spellers, and poor readers tend to be poor spellers. Several studies have documented that reading and spelling are strongly associated with each other in different languages and age groups (e.g., Babayiğit & Stainthorp, 2010;Cardoso-Martins & Pennington, 2004;Desimoni, Scalisi, & Orsolini, 2012;Furnes & Samuelsson, 2011;Georgiou, Torppa, Manolitsis, Parrila, & Lyytinen, 2012;Landerl & Wimmer, 2008;Leppänen, Niemi, Aunola, & Nurmi, 2006;Vaessen & Blomert, 2013;Yeung et al, 2011). However, the imperfect correlation between the two (rs range from .60 to .80; see meta-analysis by Swanson, Trainin, Necoechea, & Hammill, 2003) leaves open the window for a dissociation in which good readers can also be poor spellers (known as unexpected poor spellers) and poor readers can also be good spellers (known as unexpected poor readers).…”
mentioning
confidence: 99%
“…The close connection between reading and spelling has been documented by many studies in different writing systems (e.g., Babayiğit & Stainthorp, 2010;CardosoMartins & Pennington, 2004;Conrad, 2008;Ehri, 1997;Georgiou et al, 2011;Leppänen, Niemi, Aunola, & Nurmi, 2006;Vaessen & Blomert, 2013). In a meta-analysis, Swanson, Trainin, Necoechea, and Hammill (2003) reported that the average observed correlation between word reading and spelling was 0.70.…”
Section: Introductionmentioning
confidence: 80%
“…If spelling is attention demanding, and therefore draws processing resources away from higher-level processes, the writer may, in a literal sense, forget what they were going to say. This trade-off between transcription (spelling and handwriting) and higher-level conceptual or rhetorical processing has frequently been argued (e.g., Berninger, 1999;McCutchen, 1996;Torrance & Galbraith, 2006;von Koss Torkildsen, Morken, Helland, & Helland, 2016), although evidence of a causal relationship between spelling competence and text quality (spelling accuracy aside) is not yet established (see, for example, Babayiǧit & Stainthorp, 2010;Graham & Santangelo, 2014).…”
Section: Introductionmentioning
confidence: 99%